GRAMMATICAL ERROR OF SPEECH BY STUDENTS IN BILINGUAL PROGRAM OF MA’HAD AL JAMI’AH UIN NORTH SUMATRA - Riyah Sibha Nasution; Rahmad . Husein; Anni Holila Pulungan (Universitas Negeri Medan, 2021)
This study investigates the types of grammatical errors produced by Arabic learners in English. Bilingual program is a condition that the students speak both English and Arabic languages in their daily communication. The researcher used descriptive qualitative research in conducting this study. The data are bilingual students’ utterances consisting of grammatical errors in daily communication. The utterances consisted of words, phrases, clauses and sentences. The prior aim in this research is to describe the types of grammatical errors since there are two kinds of grammatical errors namely morphological errors and syntactical errors.Keywords: Grammatical Error, Bilingualism, English, Arabic language, Speech